P Pengaruh Metode Permainan Find Your Mate Terhadap Peningkatan Pengetahuan Kader Posyandu Tentang Lima Meja Di Puskesmas Klasaman Kota Sorong Tahun 2019 - Vera Iriani Abdullah; Adriana Septiani Tambunan (Jurnal Kesehatan Indonesia, 2020)
The purpose of this research is to find out whether there is an influence of the game find your mate method to increase the knowledge of Integrated Services Post cadres about five tables. The type uses quasi-experimental design (Quasi Experiment), that is the experimental action aims to find out a phenomenon or reality in the consequences caused by a particular treatment. By using a comparative class design (one group pretest-posttest design) using a preliminary test and a final test so that the effects of a treatment can be known. In this design, the combined members of the pilot in the treatment group are not done randomly. The primary data is obtained through a questionnaire. The secondary data is obtained from the Integrated Services Post of Klasaman Sorong as a research site. The population in the Integrated Services Post cadre study was 28 people with a total sample of the whole population. The results of the Paired Sample T-Test test analysis in both groups obtained p value of 0,000 (<0.05). The results showed that there was an influence of the Find your mate game method on increasing the knowledge of Integrated Services Post cadres about five tables. Keywords : Find Your Mate, Integrated Services Post Cadre, Five Tables The purpose of this research is to find out whether there is an influence of the game find your mate method to increase the knowledge of Integrated Services Post cadres about five tables. The type uses quasi-experimental design (Quasi Experiment), that is the experimental action aims to find out a phenomenon or reality in the consequences caused by a particular treatment. By using a comparative class design (one group pretest-posttest design) using a preliminary test and a final test so that the effects of a treatment can be known. In this design, the combined members of the pilot in the treatment group are not done randomly. The primary data is obtained through a questionnaire. The secondary data is obtained from the Integrated Services Post of Klasaman Sorong as a research site. The population in the Integrated Services Post cadre study was 28 people with a total sample of the whole population. The results of the Paired Sample T-Test test analysis in both groups obtained p value of 0,000 (<0.05). The results showed that there was an influence of the Find your mate game method on increasing the knowledge of Integrated Services Post cadres about five tables.